Neuroprotection Caused by Hyperoxia Preconditioning in Animal Stroke Models - Mohammad Reza Bigdeli (The Scientific World Journal)
Ischemic tolerance induced by hyperoxia (HO) can protect against brain injury and neurodegenerative diseases. Although multiple studies demonstrate neuroprotection by HO, the exact mechanism(s) of HO neuroprotection has not been elucidated. Here, I first review related mechanisms of brain ischemia and then data evaluating the neuroprotective effects of HO in focal and global ischemic animal models. I clearly establish that the cerebrovascular, extracellular matrix, plasma membrane, endoplasmic reticulum, mitochondrial, and lysosomal reactions are critical in neuroprotection induced by HO in focal ischemia. In rats and mice, the middle cerebral artery occlusion (MCAO) model was used to represent cerebrovascular stroke. Neuroprotection induced by HO exhibits specific adaptation responses that involve a number of cellular and biochemical alterations, including metabolic homeostasis and reprogramming of gene expression. The changes in the metabolic pathways are generally short lived and reversible, while the consequences of gene expression are a long-term process and may lead to the permanent alteration in the pattern of gene expression. The neuroprotection provided by HO may have important clinical implications. Therefore, it is important to assess the benefits and risks of HO therapy in noninfarcted tissue.